Localizing syndemics: A comparative study of hunger, stigma, suffering, and crime exposure in three Haitian communities. (February 2022) - Brewis, Alexandra; Wutich, Amber; Galvin, Michael; Lachaud, James
Abstract: Theoretically, disease syndemics are hyper-localized in the forms they take, but little empirical data show how localization manifests. We present a comparison across three sites in Haiti, from data collected in June–august 2017 testing for localizations of risks across three communities: rural farming, border town, and in a high gang-activity urban zone. First, we modeled survey responses collected from heads of 4055 geographically-sampled households via linear regression, considering additive and interaction effects of food insecurity, crime exposure, and discrimination on depression and anxiety levels. Exposure to food insecurity, crime exposure, and discrimination were each associated with more depression and anxiety symptoms. For those living in the urban zone, there was weak evidence of possible interactional risks between the three vulnerabilities, suggesting little meaningful localized syndemic patterning. Second, we conducted thematic and word-based semantic network analysis to identify if people themselves cognitively connected vulnerabilities of hunger/poverty, crime, and suffering/discrimination using 7321 text blocks from 95 semi-structured interviews/focus groups. Network visualization suggested people commonly connect these domains. While the patterns were localized, crime concerns were central to all networks. The domain connections expressed through people's own words were more complexly inter-related than was evident from the modeled survey data, and suggested counter-intuitive influences. The quantitative approach to modeling syndemic interactions suggests no apparent practical benefits to layering or combining local anticrime, anti-hunger, and anti-discrimination programming. However, the qualitative network analysis suggests that programming could none-the-less leverage the perceived connections across domains for more meaningful and effective interventions. For the broader study of syndemics, incorporating novel qualitative approaches clarifies that constituent processes are not just potentially localizing suffering, but are also extremely important in how people cognitively understand and organize their everyday lives. Highlights: Uses comparison of 3 Haiti communities to test for localized syndemic patterning. Poverty, discrimination, and crime exposure additively heighten anxiety/depression. Modeling of interactions in survey data suggests no clear syndemic effects. Semantic network analysis of interviews reveals perceptions of syndemic effects. Novel qualitative analyses yields different ways to recognize localized syndemic patterning.